Allergic Diseases and Internalizing Behaviors in Early Childhood - Nanda, Maya K. (Pediatrics, 2016)
BACKGROUND AND OBJECTIVES: The relationship between allergic diseases and internalizing disorders has not been well characterized with regard to multiple allergic diseases or longitudinal study. The objective of this study was to examine the association between multiple allergic diseases in early childhood with validated measures of internalizing disorders in the school-age years. METHODS: Children enrolled in the Cincinnati Childhood Allergy and Air Pollution Study underwent skin testing and examinations at ages 1, 2, 3, 4, and 7 years. At age 7, parents completed the Behavior Assessment System for Children, Second Edition (BASC-2), a validated measure of childhood behavior and emotion. The association between allergic diseases at age 4, including allergic rhinitis, allergic persistent wheezing, atopic dermatitis, and allergic sensitization, and BASC-2 internalizing, anxiety, and depression T scores at age 7 was examined by logistic and linear regression, adjusting for covariates. RESULTS: The cohort included 546 children with complete information on allergic disease and BASC-2 outcomes. Allergic rhinitis at age 4 was significantly associated with elevated internalizing (adjusted odds ratio [aOR]: 3.2; 95% confidence interval [CI]: 1.8–5.8), anxiety (aOR: 2.0; 95% CI: 1.2–3.6), and depressive scores (aOR: 3.2; 95% CI: 1.7–6.5) at age 7. Allergic persistent wheezing was significantly associated with elevated internalizing scores (aOR: 2.7; 95% CI: 1.2–6.3). The presence of >1 allergic disease (aOR: 3.6; 95% CI: 1.7–7.6) and allergic rhinitis with comorbid allergic disease(s) (aOR: 4.3; 95% CI: 2.0–9.2) at age 4 had dose-dependent associations with internalizing scores. CONCLUSIONS: Children with allergic rhinitis and allergic persistent wheezing at age 4 are at increased risk of internalizing behaviors at age 7. Furthermore, multiple allergic diseases had a dose-dependent association with elevated internalizing scores.